IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 33 TAHUN 2016 TENTANG KEBIJAKAN KOTA LAYAK ANAK - Muwarni Binti Yahya; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Pekanbaru is a city that applies child friendly policy which was proposed by Ministry of Women’s Empowerment and Child Protection of the Republic of Indonesia. The fulfillment of children’s rights was undertaken by the government in the interest of future development. A considerable amount of children’s rights violations particularly in child abuse and the lack of facilities and infrastructure towards child-friendly city. The purpose of this research is to analyze the implementation of Pekanbaru Mayor Regulation No. 33 of 2016 on Child-Friendly City Policy. The concept theory used is the implementation concept of Kusumanegara (2010:97) by enacting the concept theory based on mayor regulation which are principle and purpose, scope and objectives, institutional, and finance. Qualitative method is used in this research by using purposive sampling technique in which data collection technique covers: observation, interview, and documentation. The results of this research indicate that generally, the implementation of child-friendly city policy in Pekanbaru is fairly adequate as there are local government initiatives regarding the fulfillment of children’s rights in the form of policy, programs, and activities. Although the fulfillment of children’s rights is not fully optimal on the grounds of the lack of commitment, coordination, communication, society attentiveness, and the lack of socialization. The government ought to make commitment, communicate more intensively among task forces in child friendly city, government should be quick in responding to an occurring problem especially in fulfilling children’s rights and carry out evenly spread socialization so as to increase attentiveness and active participation in the society.Keywords : Implementation, Child Friendly City